2021
DOI: 10.1021/acsanm.1c02207
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Shaped Silver Nanoparticle Labels for Electrochemical Detection of Bioassays

Abstract: In this paper, we demonstrate the use of dualshaped silver nanoparticles (AgNPs) as detection labels for electrochemical bioassays. The key finding is that by simultaneously using AgNP labels having two different shapes, the limit of detection (LOD) for the assays is lowered compared to using either of the two shapes separately. The two shapes were silver nanocubes (AgNCs) having edge lengths of 40 ± 4 nm and spherical AgNPs (sAgNPs) having diameters of 20 ± 3 nm. Two different bioassays were examined. In both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Then, the group developed several immunosensors, where a GE/ASV electrochemical method was utilized to detect different shapes of AgNP labels. 104,[115][116][117][118][119][120][121][122] It was demonstrated that the shape of the AgNP played a crucial role in determining the detection efficiency of metalloimmunoassay based on GE/ASV process. Specifically, it was shown that the LOD and analyte detection range could be tuned by simply altering the shape of the silver nanoparticle.…”
Section: Effect Of Agnp Shape and Size On The Ge Reactionmentioning
confidence: 99%
“…Then, the group developed several immunosensors, where a GE/ASV electrochemical method was utilized to detect different shapes of AgNP labels. 104,[115][116][117][118][119][120][121][122] It was demonstrated that the shape of the AgNP played a crucial role in determining the detection efficiency of metalloimmunoassay based on GE/ASV process. Specifically, it was shown that the LOD and analyte detection range could be tuned by simply altering the shape of the silver nanoparticle.…”
Section: Effect Of Agnp Shape and Size On The Ge Reactionmentioning
confidence: 99%
“…We recently addressed this problem by using two different types of Ag labels simultaneously: spherical AgNPs and Ag nanocubes [25]. This approach was effective, because the Ag nanocubes are sensitive to the lower concentrations of NT-proBNP, while the spherical AgNPs are effective at the higher end of the risk stratification range [26]. The more general conclusion of this study was that the dynamic range of metalloimmunoassay can be tuned simply by changing the shape of the metallic labels.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3] We have been developing an electrochemical metalloimmunoassay for the heart failure biomarker N-terminal prohormone brain natriuretic peptide (NT-proBNP), which is a short peptide. [4][5][6][7] The baseline concentration of NT-proBNP in the blood of a patient depends on a number of variables, including their stage of heart failure, comorbidities, age, and race. [8][9][10][11][12] Changes in the baseline level of NT-proBNP may be an indication of disease progression, and therefore there is a need for monitoring NT-proBNP levels at home.…”
Section: Introductionmentioning
confidence: 99%
“…24 These two reagents act in concert to provide a picomolar limit of detection for NT-proBNP. 4,6 Specifically, the MµBs preconcentrate the assay conjugate over a working electrode (WE), which itself is configured over a magnet. 4,25,26 The AgNPs provide a maximum amplification factor of 250 000 upon oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation